The association between physical behavior, affective states, and contextual factors: Using ambulatory assessment to characterize moderating effects - Irina Timm; Markus Reichert; Ulrich Ebner-Priemer; Marco Giurgiu (Bern Open Publishing, 2023)
Introduction Physical behavior is a key lifestyle factor in regulating and preventing diseases across the lifespan. Researchers identified affective, cognitive, and contextual factors like weather conditions, as significant contributors in determining if individuals are physically active. However, there is scarce empirical evidence about potential associations between physical behavior and affective states influenced by weather conditions in daily life. Therefore, we investigated the within-subject association between momentary affective states and physical behavior, and weather conditions and physical behavior. Further, we additionally explored if weather conditions moderated the within-subject association between momentary affective states and subsequent physical behavior. Methods Utilizing ambulatory assessment, 79 participants completed electronic diaries about their affective states (i.e., valence, energetic arousal, and calmness) up to six times a day over five days, and their physical behavior (i.e., physical activity and sedentariness) was simultaneously recorded via accelerometers. Weather conditions (i.e., temperature and precipitation) recorded near participants' locations served as moderators in the multilevel analyses. Results We showed, that the association of affective states and physical activity was moderated by temperature. Higher temperatures enhanced the positive effects of valence on physical activity (β = .001, p = .023) and attenuated the negative effects of calmness on physical activity (β = .001, p = .021). Moreover, higher temperatures enhanced the positive effects of valence on reduced sedentary behavior (β = -0.011, p = .043). In addition, we revealed a significant positive association between temperature, as a momentary weather condition, and physical activity (β = 0.025; p = .015). Furthermore, we confirmed earlier findings associating affective states with physical behavior. Increased valence and energetic arousal were positively associated with physical activity (β = 0.007; p < .001), whereas calmness predicted lower levels of physical activity (β = -0.006; p < .001). Higher levels of calmness showed a positive association with sedentary behavior (β = 0.054; p = .003). Conclusion Moderating effects, such as higher temperatures enhancing the positive effects of valence on PA, provide mechanistic real-life insights as a basis for future health technologies. Just-in-time adaptive interventions (JITAI) offer the possibility to incorporate weather conditions and allow triggering individuals within their preferred contextual condition to promote physical activity. Such personalized real-time systems have recently been promoted by the WHO as most promising.